2016
DOI: 10.1111/are.13203
|View full text |Cite
|
Sign up to set email alerts
|

The differences in postprandial free amino acid concentrations and the gene expression of PepT1 and amino acid transporters after fishmeal partial replacement by meat and bone meal in juvenile turbot (Scophthalmus maximus L.)

Abstract: Meat and bone meal (MBM) is a high‐quality alternative protein source used to replace fishmeal (FM). However, the molecular mechanisms of over‐substituted FM by MBM resulted in growth reduction are still not clear. The objective of the study was to evaluate the effect of FM replacement by MBM on the concentration of postprandial free amino acid (FAA) and mRNA abundance of peptide and amino acid transporters in juvenile turbot (Scophthalmus maximus L.). Fish were fed with FM diet (60% FM), MBM diet (33% FM + 34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 51 publications
6
8
0
Order By: Relevance
“…It is noteworthy that the concentrations of free AA in plasma were easily influenced by nutritional state, developmental stage, and endocrine status (Bos et al, 2003;Wu, 2013). Our previous study in turbot revealed that crystalline AA addition could significantly increase the plasma free AA concentration (Song et al, 2017). Consistent with the turbot study, the present study showed that largemouth bass fed the LL diet for 8 weeks presented significantly lower concentration of total EAA, TAA, and individual AA than did fish fed the LS diet.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is noteworthy that the concentrations of free AA in plasma were easily influenced by nutritional state, developmental stage, and endocrine status (Bos et al, 2003;Wu, 2013). Our previous study in turbot revealed that crystalline AA addition could significantly increase the plasma free AA concentration (Song et al, 2017). Consistent with the turbot study, the present study showed that largemouth bass fed the LL diet for 8 weeks presented significantly lower concentration of total EAA, TAA, and individual AA than did fish fed the LS diet.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, peptide and AA transporters, as the bridge connecting the internal and exterior cell milieu, are the AA sensing mechanisms that lie upstream of the TOR and AAR pathways (Castagna et al, 1997;Russell et al, 2003). In recent years, peptide and AA transporters have been considered as the first step for AA sensing and are increasingly thought to play a pivotal role in body nutrient sensing (Bröer, 2008;Song et al, 2017). In mammals, numerous reports have revealed the regulatory mechanism of dietary lysine levels on nutrient-sensing signaling pathways (Sato et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Yamamoto, Unuma, and Akiyama () reported that the appearance of plasma‐free AA peak time in rainbow trout was delayed when fishmeal in feed had been replaced by plant protein sources, which was largely in agreement with other studies on turbot (Song et al, ; Xu, He, et al, ). According to the results of Song et al () and Xu, He, et al (), decreased postprandial influx of free AAs, particularly EAAs, may lead to reducing growth and feed utilization when turbot was fed a plant protein‐based diet.…”
Section: Discussionsupporting
confidence: 76%
“…Yamamoto, Unuma, and Akiyama () reported that the appearance of plasma‐free AA peak time in rainbow trout was delayed when fishmeal in feed had been replaced by plant protein sources, which was largely in agreement with other studies on turbot (Song et al, ; Xu, He, et al, ). According to the results of Song et al () and Xu, He, et al (), decreased postprandial influx of free AAs, particularly EAAs, may lead to reducing growth and feed utilization when turbot was fed a plant protein‐based diet. As a per‐digested protein, fish fed FPH diets showed faster and higher concentrations of plasma‐free AAs compared with fish fed intact protein diets containing raw fish or fishmeal (Espe, Lied, & Torrissen, ; Espe, Sveier, Høgøy, & Lied, ; Mach & Nortvedt, ).…”
Section: Discussionsupporting
confidence: 76%
“…However, little information about ASCT2 and B 0 AT1 is available for marine fish. Previous studies have provided the gene expression profiles and dietary regulation of these two transporters in turbot, Scophthalmus maximus L. (20,21) .…”
mentioning
confidence: 99%